Em defesa da raça: práticas discursivas e estratégias no campo da medicina social em Porto Alegre (1920-1945) - Pinto, Rodrigo Teixeira (2018)
The passage from the 19th to the 20th century marks the late introduction of social medicine in Brazil in a gradual and slow way. This field of medicine characterized by its collective and preventive attributes and by the principles of eugenics and hygiene get more support between the medics in the first half of the 20th century who aims the implementation of a wide social medicine program. In Porto Alegre‟s context, although the number of medics, this field of medicine faced difficulties for its effectuation. Thus, taking as ground Michel Foucault‟s archegenealogical approach and its concepts (discursive practices, truth regime, discursive formation…) se sought to identify, delimit and analyze the intellectual production of physicians present in Porto Alegre, in its discursive aspect through scientific journals and published books in the social medicine field. Concomitantly with their intellectual production, we also identified and analyzed the implemented strategies in Porto Alegre in the delimited period, tracing the existing relations between social medicine knowledge (saber) and public health strategies present in the city between 1920 and 1945. Those objectives were guided by the hypothesis that the medic knowledge faced difficulties in Porto Alegre in its implementation as a hegemonic knowledge, in view of the presence of the positivist principles that the Partido Republicano Riograndense was driven. From the collected data throughout the research, we concluded that the decades of 1920 and 1930 were marked by a positivist truth regime where little or no space was given to social medicine and strategies of public health in Porto Alegrem while the last years of the decade of 1930 and the firsts of the next one mark a change of perspective starting with the reformulation of the Departamento Estadual de Saúde, where a medical social truth regime takes part, organizing new strategies, even though in a limited scope.